Web-Based Expert System to Diagnose Gastroenteritis in Children in Pariaman District Hospital using the Forward Chaining Method - Vicky Ariandi; Hezy Kurnia; Aulia Fitrul Hadi (Jurnal KomtekInfo, 2019)
Gastroenteritis is a digestive system disorder in the form of inflammation of the digestive system involving the stomach and small intestine. Gastroenteritis is usually called a stomach bug, gastro, or stomach virus. Although it has no connection with influenza, it is often referred to as stomach flu. Gastroenteritis is the most common digestive problem in children. Severe gastroenteritis will cause dehydration and electrolyte imbalance, this is caused by body fluids lost through diarrhea or vomiting. This system is a prototype and made as simple as possible, so that users can easily use it and redesign this expert system for other types. Because Because there are still many parents who do not know the symptoms of a disease. So an expert system was made that could diagnose early in gastroenteritis. By using a web-based forward chaining method, using this expert system, Gastroenteritis can be identified by looking at symptoms that can explain and describe whether a child is suspected of having a Gastroenteritis.